Using a tiered approach based on ecotoxicological techniques to assess the ecological risks of contamination in a subtropical estuarine protected area - Campos, B. G. [UNESP]; Cruz, A. C.F. [UNESP]; Buruaem, L. M. [UNESP]; Rodrigues, A. P.C.; Machado, W. T.V.; Abessa, D. M.S. [UNESP] (Elsevier, 2016)
This study sought to assess the ecological risks of sediments from the northern portion of an estuarine protected area (Cananéia-Iguape-Peruíbe Protected Area - CIP-PA). The CIP-PA is located on the southern coast of São Paulo State, Brazil and is influenced by former mining activities along the Ribeira de Iguape River (RIR). We used a tiered approach based on multiple lines of evidence (geochemical analyses, toxicity tests, and whole sediment toxicity identification and evaluation) in order to assess environmental quality. The sediments presented a heterogeneous composition, but the samples collected close to the RIR exhibited higher concentrations of metals (Cd, Cr, Cu, Pb) and toxicity. Multivariate analysis showed that toxicity was associated with metals, mud, organic matter, and CaCO3 quantities. The whole-sediment toxicity identification evaluation approach indicated that ammonia and metals were responsible for sediment toxicity. Overall, we concluded that the sediments collected at depositional areas fromthe northern portion of the CIP-PA presented high levels ofmetals, which originated from former mining areas located in the upper RIR basin, and that this contamination had toxic effects on aquatic invertebrates. The tiered approach was useful for identifying the degradation of sediment quality and also for indicating the causes of toxicity. Because the CIP-PA is an important estuarine protected area that is ecologically at risk, large-scale measures are required to control the sources of contamination.
Keywords: Metals; Mining; Protected area; Sediment; Whole-sediment TIE